Microbiological study of bacteriophage induction in the presence of chemical stress factors in enhanced biological phosphorus removal (EBPR). (15th September 2015) - Motlagh, Amir Mohaghegh; Bhattacharjee, Ananda S.; Goel, Ramesh
Abstract: Polyphosphate accumulating organisms (PAOs) are responsible for carrying the enhanced biological phosphorus removal (EBPR). Although the EBPR process is well studied, the failure of EBPR performance at both laboratory and full-scale plants has revealed a lack of knowledge about the ecological and microbiological aspects of EBPR processes. Bacteriophages are viruses that infect bacteria as their sole host. Bacteriophage infection of polyphosphate accumulating organisms (PAOs) has not been considered as a main contributor to biological phosphorus removal upsets. This study examined the effects of different stress factors on the dynamics of bacteriophages and the corresponding effects on the phosphorus removal performance in a lab-scale EBPR system. The results showed that copper (heavy metal), cyanide (toxic chemical), and ciprofloxacin (antibiotic), as three different anthropogenic stress factors, can induce phages integrated onto bacterial genomes (i.e. prophages) in an enriched EBPR sequencing batch reactor, resulting in a decrease in the polyphosphate kinase gene ppk1 clades copy number, phosphorus accumulation capacity, and phosphorus removal performance. This study opens opportunities for further research on the effects of bacteriophages in nutrient cycles both in controlled systems such as wastewater treatment plants and natural ecosystems. Graphical abstract: Highlights: Environmental stress factors can induce prophages integrated in PAOs genome. Copper, cyanide, and ciprofloxacin were used as stress factors. Bacteriophage induction resulted in a decrease in the polyphosphate kinase gene. Phosphorus removal performance of the EBPR was decreased following phage induction.